Strengthening Product Branding and Marketing Optimization Through Social Media on Bamboo Straw Crafts in Abuan Bangli Village - Putri Ekaresty Haes; I Gusti Ngurah Agung Adhi Krisna Murti (Universitas Negeri Semarang, 2023)
The distribution of goods and services requires marketing to reach potential customers. The development of internet technology has expanded the marketing of goods and services from traditional to online markets. The bamboo straw craftsmen in Abuan Bangli Village realized that marketing their products online needed to be done to increase the market share of their handicraft products which are currently distributed offline. The National Education University Real Work Lecture Team (KKN) conducted